KOMPOSISI DAN STRUKTUR VEGETASI HUTAN RIPARIAN SEMPADAN SUNGAI KIRAM KABUPATEN BANJAR - Anggi Nur Priosejati; Ahmad Jauhari; Kissinger Kissinger (Universitas Lambung Mangkurat, 2023)
This riparian vegetation can affect the development of river ecosystems. The role of riparian vegetation in the ecosystem, among others, is to control erosion, prevent flooding, absorb pollutants carried by water and improve the quality of river water and soil around the river. This study aims to make an inventory of vegetation types in riparian forests in order to analyze the composition and structure of vegetation. The method used in data collection is purposive sampling and plot lines. While the calculation and data analysis using the J curve and INP. This research was conducted at the river border of Kiram Village, Banjar Regency. The results of the J curve with the number of types of seedlings as many as 252 species and yields as many as 630,000 species per hectare, saplings as many as 145 species and yields as many as 58,000 species per hectare, poles as many as 74 species and yields as many as 7400 species per hectare, trees as many as 51 the number of species has a yield of 1275 the number of species per hectare. The research showed that the species that were inventoried were categorized starting from 19 species/4m2 seedlings with a total of 252 stems/4m2, 25 types/25m2 saplings with 167/25m2 stems, 19 species/100m2 poles with a total of 74 stems/100m2 and trees as many as 25 species/400m2 with a total of 51 stems/400m2. The highest Importance Value Index (INP) was at the seedling level, namely Petindis Plant Types at 44.44 percent, at the sapling level, namely Sari Departure Plants at 11.03%, at the pole level, namely Alaban Plant Types at 103.59% and at the tree level. Namely the Madang Puspa plant species by 165.85%.Vegetasi riparian ini dapat mempengaruhi perkembangan ekosistem sungai. Peran vegetasi riparian dalam ekosistem antara lain sebagai pengontrol erosi, mencegah terjadinya banjir, menyerap zat pencemar yang terbawa air serta memperbaiki kualitas air sungai dan tanah di sekitar sungai. Penelitian ini bertujuan untuk Mengiventarisasi jenis vegetasi pada hutan riparian guna menganalisis komposisi dan struktur vegetasi. Adapun metode yang digunakan dalam pengambilan data adalah purposive sampling dan plot berjalur. Sedangkan perhitungan dan analisa data menggunakan kurva J dan INP. Penelitian ini dilaksanakan di sempadan sungai Desa Kiram Kabupaten Banjar. Hasil kurva J dengan jumlah jenis semai sebanyak 252 jumlah jenis dan memiliki hasil sebanyak 630.000 jumlah jenis perhektar, pancang sebanyak 145 jumlah jenis dan memiliki hasil sebanyak 58.000 jumlah jenis perhektar, tiang sebanyak 74 jumlah jenis dan memiliki hasil sebanyak 7400 jumlah jenis perhektar, pohon sebanyak 51 jumlah jenis memiliki hasil sebanyak 1275 jumlah jenis perhektar. penelitian menunjukkan jenis-jenis yang terinventarisasi pada pengkategorian mulai dari semai sebanyak 19 jenis/4m2 dengan jumlah 252 batang/4m2, pancang sebanyak 25 jenis/25m2 dengan jumlah 167/25m2 batang, tiang sebanyak 19 jenis/100m2 dengan jumlah 74 batang/100m2 dan pohon sebanyak 25 jenis/400m2 dengan jumlah 51 batang/400m2 . Indeks Nilai Penting (INP) tertinggi pada tingkat semai yaitu Jenis Tumbuhan Petindis sebesar 44,44%, pada tingkat pancang yaitu Jenis Tumbuhan Sari Berangkat sebesar 11,03%, pada tingkat tiang yaitu Jenis Tumbuhan Alaban sebesar 103,59% dan pada tingkat pohon yaitu Jenis Tumbuhan Madang Puspa sebesar 165,85%.